Practical genetic counselling - Harper, Peter S (Oxford University Press, 2004)
The counselling of those at risk from inherited disorders forms an integral and expanding part of medicine, and advances are continually being made in this area of practice. Increasingly, common disorders are known to have a genetic component, and this book provides invaluable up-to-date guidance through the profusion of new information, and the associated psychosocial and ethical considerations and concerns. Changes for the sixth edition include full coverage of the implications of the human genome project for clinical genetic practice, the expanding societal implications of human genetics, and increased coverage of genetics and common diseases, including cancer genetics. The layout of the book has been much improved and modernized, with line illustrations redrawn throughout.
Keywords: lékařská genetika; genetika, lékařská genetika; Genetics, Medical